B(C6F5)3-catalyzed dehydrogenative cyclization of N-tosylhydrazones and anilines via a Lewis adduct: a combined experimental and computational investigation. Issue 34 (16th July 2019) - Guru, Murali Mohan; De, Sriman; Dutta, Sayan; Koley, Debasis; Maji, Biplab
Abstract : Metal-free acceptorless-dehydrogenative cyclization of N -tosylhydrazones and aromatic amines produces both symmetrical and unsymmetrical 1, 2, 4-triazoles in high yields and selectivities. Abstract : Tris(pentafluorophenyl)borane-catalyzed dehydrogenative-cyclization of N -tosylhydrazones with aromatic amines has been disclosed. This metal-free catalytic protocol is compatible with a range of functional groups to provide both symmetrical and unsymmetrical 3, 4, 5-triaryl-1, 2, 4-triazoles. Mechanistic experiments and density functional theory (DFT) studies suggest an initial Lewis adduct formation of N -tosylhydrazone with B(C6 F5 )3 followed by sequential intermolecular amination of the borane adduct with aniline, intramolecular cyclization and frustrated Lewis pair (FLP)-catalyzed dehydrogenation for the generation of substituted 1, 2, 4-triazoles.